: ( 9/4 + 16/5 + 25/6 ) - ( 5/4 - 14/5 + 47/8 ) =0. 78125
Câu hỏi tương tự Đọc th\(\left(\frac{9}{4}+\frac{16}{5}+\frac{25}{6}\right)-\left(\frac{5}{4}-\frac{14}{5}+\frac{47}{8}\right)\)
\(=\frac{9}{4}+\frac{16}{5}+\frac{25}{6}-\frac{5}{4}+\frac{14}{5}-\frac{47}{8}\)
\(=\left(\frac{9}{4}-\frac{5}{4}\right)+\left(\frac{16}{5}+\frac{14}{5}\right)+\left(\frac{25}{6}-\frac{47}{8}\right)\)
\(=1+6-\frac{41}{24}\)
\(=7-\frac{41}{24}=\frac{127}{24}\)
(\(\frac{9}{4}+\frac{16}{5}+\frac{25}{6}\)) -(\(\frac{5}{4}-\frac{14}{5}+\frac{47}{8}\))
=\(\frac{9}{4}+\frac{16}{5}+\frac{25}{6}-\frac{5}{4}+\frac{14}{5}-\frac{47}{8}\)
=\(\frac{9-5}{4}+\frac{16+14}{5}+\frac{25}{6}-\frac{47}{8}\)
= 1 + 6+\(\frac{200-282}{48}\)
=\(\frac{336-82}{48}\)
=\(\frac{254}{48}\)
=\(\frac{127}{24}\)